Troubadour on the Road to Gold : William B. Lorton's 1849 Journal to California - Lorton, William B., 1828-1892 (Book collections on Project MUSE., 2020)
"Troubadour on the Road to Gold is a true, western adventure story with lots of action and rich detail. William Lorton's spritely, detailed, and insightful journal is a delight, yet moving at the same time. He gives insight rarely found in a young man into daily trail life from the Mississippi River to southern California, by way of Salt Lake City, in the early gold rush of 1849. Additional information is added in his letters from the trail to The New York Sun newspaper. Only a couple other diarists approach Lorton's deep level of detail about the Southern Route from SLC to LA. He is an active observer who exposes the damage done from stampedes, notes variations among the Indians, feels the pleasure of a river swim in the hot sun, appreciates a beautiful sunset or a rampaging hail storm, and he provides entertaining sketches of locations that interested him. He graphically describes his disastrous "walkabout" into uncharted Nevada desert that only four dozen other men experienced before retreating to the Old Spanish Trail. He reveals his scientific curiosity in vivid descriptions of a sidewinder rattle snake, mysteriously moving rocks on a desert playa, or microscopic fairy shrimp in an ephemeral lake. Lorton is a likable fellow with a droll sense of humor who entertains the camp with his rich singing voice and ability to play the violin. At the same time he can cook, clean, or chase oxen while being stoic about getting a foot damaged when trampled in a stampede, having all his bacon stolen by the Indians, or having to shoot his faithful horse. He represents the best traits a man can possess-resilience in adversity, a positive attitude, and an active participant in the society he finds himself in, be it a Mormon home or a wagon mess on the trail"--Provided by publisher.